The Defense of Berlin - Smith, Jean Edward (Johns Hopkins University Press, 2019)
Originally published in 1963. In 1958 Nikita Khrushchev demanded that the United States, Great Britain, and France withdraw from West Berlin. His demands eventually resulted in the division of Germany's capital city through the building of the Berlin Wall. In The Defense of Berlin, Jean Edward Smith discusses Berlin from the time of arrangements set during the war through 1962, with an emphasis on the effect that the crisis of division had on the city.